Plasma Membrane Ca2+ Pump PMCA4z Is More Active Than Splicing Variant PMCA4x - Corradi, Gerardo R.; Mazzitelli, Luciana R.; Petrovich, Guido D.; de Tezanos Pinto, Felicitas; Rochi, Lucia; Adamo, Hugo P. (Frontiers in Cellular Neuroscience, 2021)
The Plasma Membrane Ca2+ pumps (PMCA) are P-ATPases that control Ca2+ signaling and homeostasis by transporting Ca2+ out of the eukaryotic cell. Humans have four genes that code for PMCA isoforms (PMCA1-4). A large diversity of PMCA isoforms are generated by alternative mRNA splicing at sites A and C. The different PMCA isoforms are expressed in a cell-type and developmental specific manner and exhibit differential sensitivity to a great number of regulatory mechanisms. PMCA4 has two A splice variants, the forms “x” and “z”. While PMCA4x is ubiquitously expressed and relatively well studied, PMCA4z is less characterized and its expression is restricted to some tissues like brain and heart muscle. PMCA4z lacks a stretch of 12 amino acids in the so-called A-M3 linker, a conformation sensitive region of the molecule connecting the actuator domain (A) with the third transmembrane segment (M3). We expressed in yeast PMCA4 variants “x” and “z”, maintaining constant the most frequent splice variant “b” at the C-terminal end, and obtained purified preparations of both proteins. In the basal autoinhibited state PMCA4zb showed a higher ATPase activity and a higher apparent Ca2+ affinity than PMCA4xb. Both isoforms were stimulated by calmodulin, but PMCA4zb was more strongly activated by acidic lipids than PMCA4xb. The results indicate that a PMCA4 intrinsically more active and more responsive to acidic lipids is produced by the variant “z” of the splicing site A